2012
DOI: 10.1073/pnas.1121201109
|View full text |Cite
|
Sign up to set email alerts
|

Foraging success of biological Lévy flights recorded in situ

Abstract: It is an open question how animals find food in dynamic natural environments where they possess little or no knowledge of where resources are located. Foraging theory predicts that in environments with sparsely distributed target resources, where forager knowledge about resources' locations is incomplete, Lévy flight movements optimize the success of random searches. However, the putative success of Lévy foraging has been demonstrated only in model simulations. Here, we use high-temporal-resolution Global Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
364
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(378 citation statements)
references
References 30 publications
12
364
1
1
Order By: Relevance
“…For phages, the search for a susceptible bacterial host is effectively "blind." When limited to random searching, the chance for a successful predator-prey encounter depends largely on the search strategy used (33). In this situation, many motile predators, ranging from microbes to humans, use Lévy flight, a superdiffusive search strategy, to increase their success (28,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…For phages, the search for a susceptible bacterial host is effectively "blind." When limited to random searching, the chance for a successful predator-prey encounter depends largely on the search strategy used (33). In this situation, many motile predators, ranging from microbes to humans, use Lévy flight, a superdiffusive search strategy, to increase their success (28,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…ubiquity of Lévy patterns among extant organisms, including humans (1)(2)(3)(12)(13)(14)(15)(16)(17)(18), suggests that searches that approximate them have evolved naturally (3). It has been hypothesized that behavioral adaptations to changes in environmental resources cue the switching between localized Brownian and Lévy random searching (2,3,13) or that sensory interactions with heterogeneous environments may give rise to Lévy movement patterns (an emergent phenomena) (19); however, the origins of such potential mechanisms remain elusive.…”
mentioning
confidence: 99%
“…Numerous recent papers have demonstrated that foraging animals in the wild or under controlled conditions show path lengths consistent with power laws (5)(6)(7)(8)(9)(10)(11), which are proposed to arise from an underlying Lévy walk process. Theoretical models have demonstrated that such a process can be optimal for memoryless agents searching for randomly distributed rewards across space under certain conditions (1,2,12).…”
mentioning
confidence: 99%
“…Because power law path lengths have been observed in sparse and dynamic environments (e.g., open ocean), in which foragers rarely revisited previously rewarded locations (8,10,21,22), it is reasonable to assume, as foundational models have, that there is little advantage to learning about the reward distributions at any given spatial location. Hence, under this assumption, prior studies constrained the class of models studied to random searches in the absence of learning.…”
mentioning
confidence: 99%